Impacts of Internal Control and Risk Management on Real Estate and Construction Sector in Vietnam - Dinh, Trung Van; Tha, To Hien; Nguyen, Trang Thuy; Dinh, Trang Thi Nhu (International Journal of Membrane Science and Technology, 2023)
Transparency and disclosure of accounting information in Vietnamese enterprises have been becoming one of hot issues in recent years, as it will affect risk and investment , for instance in a specific industry such as real estate sector in Vietnam. The reliability and availability of these data will facilitate better internal control and risk management procedures and activities for quality control of real estate projects in such emerging markets as Vietnam. We will mainly use statistic and qualitative analysis methods including synthesis and inductive methods to evaluate effects of internal control and risk management on real estate sector, both positive and negative sides. The results show us that This research finding and recommended policy also can be used as reference in policy for internal control and risk management in many developing countries.